#TITLE_ALTERNATIVE# - ILAHI (NIM : 20112021) ; Pembimbing Prof.Dr.Edy Soewono, FADILAH
Ujung Kulon National Park (TNUK) is the last wildlife sanctuary for Javan rhino (Rhinoceros sondaicus). Recent report from the TNUK indicates that the rhino population remains stagnant at the level of 50s for long period of time. In this thesis, the author tries to represent the state of the Javan rhino population in Ujung Kulon National Park using lo- gistic type equation associated with the presence of wild bull (Bos javanicus) populations. Here the model of carrying capacities are function of both species. Analysis of co-existence and its stability are done here. Numerical simulation is shown to provide an overview of the interactions that occur between the two species above. The results obtained from this modeling conclude that carrying capacity of each species changes in time and eventually converges along with the stability of the co-existence equilibrium.